2011
DOI: 10.1016/j.ijid.2011.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis and diabetes in Guyana

Abstract: This study clearly highlights that diabetes and HIV are frequent in Guyanese TB patients. Routine screening of TB patients for diabetes and diabetic patients for TB should be speedily implemented. The National TB Programme should work closely with the diabetes clinics so that TB patients who are diabetics are optimally managed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 8 publications
(12 reference statements)
2
16
1
1
Order By: Relevance
“…Similar results were reported by Patel et al during his study conducted in Indian population that majority patients of TB-DM were male (73.68%) while female were the minority (26.32%). Moreover, similar results were obtained from another study conducted in Pakistan by Jabbar et al revealed that 60.21% male patients out numbered the female participants (39.78%) in terms of TB-DM co-incidence 18 . The perevelnce of higher ratio of TB-DM may be due to the case that male are exposed to the outer environment more as compared to female and encountered by multiple infections.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Similar results were reported by Patel et al during his study conducted in Indian population that majority patients of TB-DM were male (73.68%) while female were the minority (26.32%). Moreover, similar results were obtained from another study conducted in Pakistan by Jabbar et al revealed that 60.21% male patients out numbered the female participants (39.78%) in terms of TB-DM co-incidence 18 . The perevelnce of higher ratio of TB-DM may be due to the case that male are exposed to the outer environment more as compared to female and encountered by multiple infections.…”
supporting
confidence: 85%
“…The results of present study are similar to those of Amin et al that reported co-occurrence of TB and DM in 14% patients of Peshawar, Pakistan 6 . Similarly, another study of Pakistani population conducted by Jabbar et al in 2006 showed co-occurrence of TB and DM among 11.9% study participants 18 .…”
Section: Fig1 Overall Prevalence Of Diabetes Among Tb Patientsmentioning
confidence: 77%
“…There were five (6.4%) studies from Oceania that showed prevalence rates ranging from 12% in Fiji [104] to 45% in Ebeye-Marshall Islands [103] and the overall median prevalence in this area was 23.2% (IQR 12.8%-39.0%). Three (3.8%) studies conducted in South America indicated prevalence rates ranging from 6.1% in Brazil to 14% in Guyana [98,101]. This amounted to an overall median prevalence of 11.1% (IQR 6.1%-14.0%).…”
Section: Resultsmentioning
confidence: 99%
“…18,19 Studies that have assessed radiological differences between TB patients with and without DM have noted that cavities are more common in TB patients with DM; this may also influence sputum smear status. 20,21 While data may be conflicting, there is some evidence to suggest that DM influences the clinical presentation of TB.…”
Section: Public Health Action Tb and Diabetes In Fiji 161mentioning
confidence: 99%